RAINFALL MODELLING IN EAST JAVA USING A MODIFIED ORNSTEIN-UHLENBECK MODEL - Setyorini, Elisabeth Yeyen; Putri, Endah R. M. (Departemen Matematika dan Sains Data FMIPA Universitas Andalas Padang, 2025)
One of the current global issues is climate change and weather variability. This phenomenon has real impacts on various regions, including East Java Province. East Java is experiencing increased rainfall intensity as one of the effects of climate change. High and continuous rainfall intensity can trigger disasters such as flooding, which has the potential to cause significant financial losses for the community. Therefore, effective risk management becomes crucial. One possible solution to address these risks is through the use of financial derivatives. The initial step in risk management involves modeling the behavior of rainfall. It is assumed that the rainfall pattern follows a mean-reverting process, specifically the Ornstein-Uhlenbeck process. The existing Ornstein-Uhlenbeck model is then modified to ensure that the resulting model accurately reflects the rainfall conditions in East Java. To validate the modified model, simulations of the Ornstein-Uhlenbeck process were conducted using estimated parameter values. The Ornstein-Uhlenbeck simulation achieved a minimum MSE score that approaches zero. This MSE score indicate that the proposed modified Ornstein-Uhlenbeck model is accurate in representing the rainfall patterns in East Java.